Tachydromia maculipennis Walker 1849 - Shamshev, Igor V.; Grootaert, Patrick (Zenodo, 2024)
Tachydromia maculipennis Walker (Fig. 10) Tachydromia maculipennis Walker, 1849: 507. Type locality: Canada, St. Martin’s Falls, Albany River, Hudson’s Bay (after Smith 1971: 367). Tachypeza pusilla Loew, 1864b: 87 [Cent. 5, no. 74]. Type locality: USA, Illinois. Tachydromia pusilla (Loew): Melander, 1910: 52 (synonymy). Phoneutisca bimaculata Loew: Melander, 1902: 204. Misidentification. Type material examined. Smith (1971: 367) provided data about the holotype of this species, which is represented only by two legs. Data on the syntype of Tachypeza pusilla Loew (including photos of labels and habitus) are available from the database of insect primary types in the collection of MCZ (https://mczbase.mcz.harvard.edu/ guid/ MCZ:Ent:1168). Additional material examined. CANADA. Manitoba: Aweme, 14.vi.1924, R.D. Bird (2 ♂, 2 ♀, CNC); 2 mi. W Stockton, 26.v.1958, C.D.F. Miller (1 ♂, CNC); 5 mi. SW Chilo, ex choke-cherry, floodplain community nr. Tamarack Bog, 5.vi.1958, J.F. McAlpine (1 ♂, 7 ♀, CNC); 2 mi. W Stockton, ex flowers Erysimum aspersum , 26.v.1958, J.F. McAlpine (1 ♂, 1 ♀, CNC); Ninette, ex. Amelanchier blossoms, 16.v.1958, J.F. McAlpine (1 ♀, CNC). Ontario: Hog’s Back, 9.vi.1923, R. Ozborn (1 ♀, CNC); Chatham, 18333.D, 28.v.1928, A.B. Baired (1 ♀, CNC); same locality, 18333.D, 1.vi.1928, A.B. Baired (1 ♂, CNC); Simcoe, 29.v.1939, G.E. Shewell (1 ♂, 6 ♀, CNC); same locality, 2.vi.1939, G.E. Shewell (1 ♀, CNC); same locality, 3.vi.1939, G.E. Shewell (2 ♂, 4 ♀, CNC); same locality, 5.vi.1939, G.E. Shewell (2 ♂, 2 ♀, CNC); same locality, 9.vi.1939, G.E. Shewell (1 ♀, CNC); same locality, host Spiraea , 18.vi.1939, G.E. Shewell (3 ♀, CNC); Ottawa, 1.vi.1939, O. Peck (1 ♀, CNC); Manotick, taken from Malaise trap, 27.v.1952 (3 ♂, 9 ♀, CNC); Marmora, Hawthorn, 29.v.1952, G.E. Shewell (1 ♂, CNC); Manotick, Malaise trap, vi.1952, J.F. McAlpine (2 ♂, CNC); Maynooth, host Spiraea , 18.vi.1953, J.F. McAlpine (9 ♂, 10 ♀, CNC); Ottawa, 31.v.1954, J. R. Vockeroth (1 ♂, CNC); Midland, 20.5.1959, J.G. Chillcott (1 ♀, CNC); ...